Towards a non-Brahmin millennium : from Iyothee Thass to Periyar - Kītā, Va (Samya ; in association with Book Review Literary Trust ; Distributed by Bhatkal Book International, 1998)
On non-Brahmin-Dravidian movement in Tamil Nadu, India.